SmMYB113 Is a Key Transcription Factor Responsible for Compositional Variation of Anthocyanin and Color Diversity Among Eggplant Peels - Yang, Guobin; Li, Lujun; Wei, Min; Li, Jing; Yang, Fengjuan (Frontiers in Plant Science, 2022)
To understand the color formation mechanism in eggplant (Solanum melongena L.) peel, a metabolomic analysis was performed in six cultivars with different peel colors. A total of 167 flavonoids, including 16 anthocyanins, were identified based on a UPLC-MS/MS approach. Further analysis revealed that the delphinidins/flavonoids ratio was consistent with the purple coloration of eggplant peels, and SmF3’5’H ex-pression level was consistent with the delphinidin 3-O-glucoside and delphinidin 3-O-rutinoside contents, the main anthocyanins in the purple-peels eggplant cultivars identified in this study. SmMYB113 overexpression promoted anthocyanins accumula-tion in eggplant peels and pulps. Metabolomic analysis revealed that delphinidins were still the main anthocyanins class in the peels and pulps of SmMYB113-OE4, but most anthocyanins were glycosylated at the 5-position of the B-ring. Our results provide new insights into the anthocyanin composition of eggplant peels and demonstrate the importance of SmMYB113 in stimulating anthocyanin biosynthesis in eggplant fruits.